(untitled) (Academicia Globe: Inderscience Research, 2021)
According to official data, the incidence of cutaneous leishmaniasis is the last 5 years; in endemic areas, Uzbekistan is growing markedly. Given the increase in the incidence rate among the population of the republic, it is necessary to conduct an annual epidemiological analysis of the detection and spread of this disease, with the aim of timely monitoring and prevention. [1,4,5]